Systematics of Martinella Baill. (Bignonieae, Bignoniaceae) - Kataoka, Eric Yasuo (2019)
Martinella Baill. is a small genus of Neotropical lianas within tribe Bignonieae (Bignoniaceae). The genus is monophyletic, well supported by morphological and molecular characters. Members of Martinella have a continuous interpetiolar ridge surrounding the stem, bilobed or 4-5-parted calyces, and minute triangular prophylls of the axillary buds. The most recent taxonomic treatment of Martinella recognized three species: Martinella insignis A.H. Gentry ex Zuntini & L.G. Lohmann, endemic to the Atlantic Forest of eastern Brazil, Martinella iquitoensis A. Samp. [= Martinella insculpta Sprague & Sandwith], and Martinella obovata (Kunth) Bureau & K. Schum., the latter two are widely distributed species from southern Mexico to Bolivia. Generic circumscription remained unchanged since the description of Martinella, although species delimitation and phylogenetic relationships among species within the genus remained unclear or unknown. In this dissertation, I investigated phylogenetic relationships of Martinella, and conducted a taxonomic revision. The phylogenetic reconstruction was based on a hybrid approach that combined high throughput sequencing (HTS) with Sanger sequencing data to infer the phylogeny of Martinella based on broad sampling of characters and individuals. Three complete and three nearly-complete plastomes were sequenced, assembled, and annotated. In addition, sequences of the plastid markers ndhF and rpl32-trnL and the nuclear marker pepC were obtained for additional samples, covering the morphological diversity and geographic distribution of members of the genus. The tree that resulted from the analysis of the complete dataset (Sanger + HTS) is fully resolved, representing the most robust estimate of phylogenetic relationships of Martinella to date. This phylogeny identified five main clades that are recognized as five species in the taxonomic revision of the genus. These five species represent the three previously recognized species plus two new species, Martinella lanuginosa Kataoka & L.G. Lohmann and Martinella tomentosa Kataoka & L.G. Lohmann. The taxonomic revision of the genus presents detailed descriptions for all five taxa, a complete list of synonyms, distribution maps, illustrations, and indications of conservation status for all species recognized. This thesis highlights the importance of in-depth taxonomic studies of selected lineages, especially in megadiverse regions such as the Neotropics, where sampling lacunae still persist